Business risks level of consequences identification: case of women formal fashion smes in Bandung and Jabodetabek - Putri, Ghaissani Elsa; Darmansyah, Asep (Journal of Innovation, Business and Entrepreneurship, 2019)
Fashion SMEs is one of the creative industry sectors in Indonesia that contributes high to the gross domestic product (GDP). Based on a study, inexperienced people (in this case, fashion SMEs) usually do not see the risks that might occur, or if they do, they underestimate the possibility that they will be affected by them. This study aims to identify business risks and their level of consequences in women's formal fashion SMEs. This research use a qualitative approach with in-depth interview methods. Based on the research known from the five risk categories according to the reference literature, each has a different level of impact. This level of consequences is strongly influenced by the condition of the business scale, business models, vision and mission.Keyword:Business Risk, Risk Identification, Risk Level of Consequences, Small and Medium Enterprises, Women Formal Fashion